PENGEMBANGAN STRATEGI PEMASARAN DAYA TARIK WISATA SANGEH, ABIANSEMAL, BADUNG - I Wayan Pantiyasa; I Made Arnawa (Institut Pariwisata dan Bisnis Internasional, 2016)
Sangeh travel attractions tends to decrease the number of visitors, therefore it requires an innovative strategy to promote the tourism object. The aim of this study is to create alternative strategy in promoting Sangeh travel attraction. The data in this study was collected through deep interview and note taking or document recording. Then the data was analyzed using qualitative descriptive by giving explanation or interpretation from the data obtained. Therefore, the data was not only in term of numbers, but also there was a clear explanation of the numbers. In this study also used SWOT IFAS (Internal factor analysis summary) and EFAS (Eksternal factor analysis summary) and SWOT matrix technique in analyzing data. The result of the study shows that Sangeh had not taken the opportunities maximally. The opportunities such the strategy route which is located around Sangeh is not maximal use. The promotion strategy applied through website with no update information by administrator. Besides that, in promoting the tourism object only involves the guest without doing any innovative ways in promoting the product. The highest weakness is there is no cooperation with travel agency. Besides that, external threat includes many similar tourism objects with more attractive products.